Model Kepemimpinan Transformatif dalam Menciptakan Inovasi Pengembangan Kelembagaan Pendidikan Islam - Zainullah Zainullah; Moh Mahfud; Artamin Hairit (Kuttab : Jurnal Ilmu Pendidikan Islam, 2020)
The era of the industrial revolution 4.0, accompanied by the advancement of information and communication tools today, is both an opportunity and a challenge for Islamic educational institutions to progress and develop. If an Islamic educational institution does not improve and does not respond well to the flow of development, it will be eroded by time (abandoned by the community). The purpose of writing this article is to reconstruct the transformative leadership model in creating the ideal institutional development of Islamic education. This research is in the form of a descriptive qualitative form using content analysis methods to find its relevance to the transformative leadership model in the world of Islamic education today. The results of this study are transformative leadership is one of the leadership styles that need to be applied in the development of Islamic educational institutions. So that it can make a change or innovation that can respond to the development of the times followed by the development and development of information tools and technology. Islamic educational institutions that cannot improve "writhing" in response to the times or are only managed traditionally "Tombo Ati", will be crushed by the times or abandoned by the community.